2011
DOI: 10.1007/s00253-011-3535-5
|View full text |Cite
|
Sign up to set email alerts
|

Methanotrophic community structure and activity under warming and grazing of alpine meadow on the Tibetan Plateau

Abstract: Knowledge about methanotrophs and their activities is important to understand the microbial mediation of the greenhouse gas CH(4) under climate change and human activities in terrestrial ecosystems. The effects of simulated warming and sheep grazing on methanotrophic abundance, community composition, and activity were studied in an alpine meadow soil on the Tibetan Plateau. There was high abundance of methanotrophs (1.2-3.4 × 10(8) pmoA gene copies per gram of dry weight soil) assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
46
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(55 citation statements)
references
References 58 publications
7
46
2
Order By: Relevance
“…These CH 4 consumption values were within the upper range of CH 4 flux rates observed by previous studies on the Tibetan Plateau [9,[20][21][22]. The soil has a much higher content of organic carbon on the plateau than other grassland soils in China [23], which leads to a higher abundance of methanotrophs in alpine meadow soils [24,25] and higher soil CH 4 consumption in alpine meadows.…”
Section: Soil Ch 4 Consumptionsupporting
confidence: 59%
See 1 more Smart Citation
“…These CH 4 consumption values were within the upper range of CH 4 flux rates observed by previous studies on the Tibetan Plateau [9,[20][21][22]. The soil has a much higher content of organic carbon on the plateau than other grassland soils in China [23], which leads to a higher abundance of methanotrophs in alpine meadow soils [24,25] and higher soil CH 4 consumption in alpine meadows.…”
Section: Soil Ch 4 Consumptionsupporting
confidence: 59%
“…Here we analyzed the effects of UV radiation on CH 4 fluxes, in this study the CH 4 consumption by soils in all four plant communities showed a significantly positive correlation with UV radiation (Fig. 5), there had been no report about this phenomenon, and the mechanism of methane consumption was methane absorbed by methane oxidative bacteria in the soil pore, UV radiation had a positive correlation with soil temperature (P<0.01), and accelerated the bacterial metabolism ability, because the temperature was the main limiting factor of bacterial metabolism on the Tibetan Plateau [24], WFPS also increased with UV radiation (P<0.01), made the soil more porous, then increased the methane consumption by meadow soil. Therefore, UV radiation can indirectly enhance CH 4 oxidation through altering soil temperature and moisture in the soil.…”
Section: Effects Of Soil Wfps and Temperature On Ch 4 Consumptionmentioning
confidence: 99%
“…Grassland is also one of the environments for growth of methanotroph: researchers found methanotroph in meadows of Qinghai-Tibet Plateau [14] and Inner Mongolia grassland [15] in China. An analysis reveals that warming and grazing exert an important effect on activity of methanotroph [14] .…”
Section: Conventional Natural Environmentmentioning
confidence: 99%
“…An analysis reveals that warming and grazing exert an important effect on activity of methanotroph [14] .…”
Section: Conventional Natural Environmentmentioning
confidence: 99%
“…For example, stable isotope labeling experiments demonstrated that type I MOB exhibit significantly higher pmoA gene expression level and growth rates than the type II, and are predominantly active in many important habitats with high methane emissions (Chen et al 2007;Qiu et al 2008;Zheng et al 2008;Kip et al 2010;Dumont et al 2011;Graef et al 2011;Zheng et al 2012;Ho et al 2013). On the other hand, the type II MOB population is relatively stable and serves as microbial seed bank in the soil (Eller et al 2005;Krause et al 2012).…”
Section: Introductionmentioning
confidence: 99%